Policy Formulation for Managing Ship-generated Plastic Waste via Improved Port Reception Facility Governance - Kurniaty, Rika; Widagdo, Setyo; Rachmawati Madjid, Yasniar; Reyhan Al Kharji, Rafly; Imanda Putri, Arsella (Indonesian Journal of International Law, 2023)
Plastic is a significant portion of marine debris, ranging from 60% to 80%. Historically, ships have been a major contributor to plastic pollution in the ocean, followed by Indonesia, which is acknowledged as the second-largest originator. Global efforts to combat marine pollution, including plastic waste, have been undertaken through international agreements like MARPOL Annex V. This agreement has mandated countries to establish suitable port facilities for ship-generated wastes. However, an assessment of Indonesian ports indicated insufficient compliance with environmental management standards, particularly in waste handling. The current direct fee policy for waste disposal may disincentivize proper waste disposal by ship operators. This research examined and analyzed standards for adequate port waste reception facilities and explored the potential of implementing an indirect fee policy to promote responsible waste disposal. The research also provided recommendations for enhancing plastic waste management in accordance with international treaties ratified by the Indonesian government. The result showed that although existing national legal instruments indirectly address plastic waste concerns, specific regulations and updates are needed. Furthermore, the introduction of indirect fee policies for waste disposal at ports, coupled with stronger law enforcement, can incentivize proper waste management practices. These policies offered a promising strategy to address the challenges posed by plastic waste and contribute to sustainable environmental practices. By adopting these policies, countries were able to take a proactive approach to mitigating plastic pollution and protecting marine ecosystems.